Implementasi Kebijakan Pemeliharaan Ruang Terbuka Hijau Oleh Pemerintah Kabupaten Jombang (Studi: Dinas PU Cipta Karya, Bidang Pertamanan di Kabupaten Jombang) - Izzati, Hatfina (Jurnal Administrasi Publik, 2016)
Abstract: The Implementation of Green Open Space Maintenance Policy by the Government of Jombang Regency (Study at the Official of Public Works, Work Creation, Spatial Order, Cleanliness, and Gardening of Jombang Regency). The government has made a program to maintain Green Open Space by conducting the programs from the center including the periodic program for vegetative planting, plant embroidery, and soil utilization by developing the park on private ownership and also by managing less maintained lands. The improvement of RTH quality is reaching 20 %. The government of Jombang Regency attempts to construct the annual master plan because there is already a design draft for Green Open Space Maintenance that explains what part of space is on priority and to be managed. This master plan will help the government to meet the percentage target stated in Local Regulation. The demand of personnel is not only met by the presence of special teams in monitoring RTH but also by building a communication between the sustainable community and the socialization of local regulation. Keywords: policy implementation, green open space Abstrak: Implementasi Kebijakan Pemeliharaan Ruang Terbuka Hijau Oleh Pemerintah Kabupaten Jombang (Studi pada Dinas Pekerjaan Umum Cipta Karya, Tata Ruang, Kebersihan, Dan Pertamanan Kabupaten Jombang). Pemerintah Kabupaten Jombang menjalankan masterplan tiap tahunnya karena sudah adanya rancangan serta pemeliharaan Ruang Terbuka Hijau mana saja yang akan diprioritaskan dan dikerjakan. Halini akan memudahkan pemerintah dalam pemenuhan prosentase yang ditetapkan dalam perda. Tidak hanya itu menambahkan personil untuk tim khusus dalam hal pengawasan RTH dan komunikasi antara masyarakat juga harus berkelanjutan serta sosialisasi tentang peraturan daerah agar masyarakat lebih memahami. Â  Kata kunci : implementasi kebijakan, ruang terbuka hijau